The Influence of Emotional Intelligence, Work Environment, and Organizational Support on Employee Performance - Wahyuningsih, Feni; Hasyim, Hasyim (Faculty of Economics and Business UNTAG Semarang, 2023)
This research aimed to determine the influence of emotional intelligence, work environment, and organizational support on employee performance at the Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Jawa Tengah. The sample for this research was 62 people taken using probability sampling techniques. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the emotional intelligence, work environment and organizational support have a significant positive effect on employee performance. This study suggests that the government should pay attention to these three factors to improve employee performance.